Nonfinancial Performance Measures as Coordination Devices - Baiman, Stanley; Baldenius, Tim (The Accounting Review, 2009)
ABSTRACT: We investigate how nonfinancial performance measures (NPMs) can be used to encourage cooperation across divisions. The implementation of a project often requires joint efforts by multiple divisions. However, privately informed division managers sometimes find it in their self-interest to forgo profitable joint projects or to underinvest in relationship-specific assets. By treating the implementation of a joint project (e.g., a major process improvement or new product development) as an NPM, we show that paying the division managers discrete bonuses tied to this NPM improves the efficiency of project implementation and upfront investments. We derive how the optimal implementation bonus trades off distortions in ex post implementation and ex ante investments. In a dynamic version of the base model with learning-by-doing, we show that conditional on a project being implemented early on, the implementation bonus in subsequent periods will be higher than if the earlier project had not been implemented.